Designing a Shariah Financing Scheme for the Development of Canary Farming: A Conceptual Study of the Murabahah and Ijarah Contract - Akbar Muhamad Ashoni; Khansa Mujahidatunnisa Sukmana (Mabahits Al-Uqud, 2025)
Canary farming has emerged as a promising micro-enterprise sector due to its economic potential and cultural value. However, the development of this business often faces obstacles related to limited access to financing that complies with Sharia principles. This conceptual paper aims to design an integrated Shariah-compliant financing model for canary farming, focusing on the application of Murabahah and Ijarah contracts. The study adopts a qualitative conceptual approach through an in-depth review and synthesis of relevant literature on Fiqh Muamalat and Islamic finance. The proposed model integrates Murabahah for asset procurement, Ijarah for facility access, Wakalah for transaction facilitation, and Rahn for collateral management, forming a comprehensive financing framework tailored to the needs of small-scale canary farmers. This model emphasizes fairness, transparency, and sustainability while promoting financial inclusion through Sharia-based cooperative mechanisms. As a conceptual framework, the proposed scheme provides theoretical insights into how Islamic financial institutions can support the livestock sector through non-interest-based financing mechanisms. Future research should empirically test this model through field implementation to evaluate its practical effectiveness and identify operational challenges in real-world contexts.